Partaking in cycling, at what cost? Determinants of cycling expenses. (2016) - Thibaut, Erik; Vos, Steven; Lagae, Wim; Puyenbroeck, Tom Van; Scheerder, Jeroen
This study analyses the determinants of cycling expenditure by means of a Tobit regression analysis, based on a dataset of 5, 157 cyclists. Using a heterodox economic approach, 23 different variables are combined into two commonly used variable groups in the field of sports expenditure (socio-demographics, sports intensity variables) and two variable groups [socio-economic cycling capital, and attitudes, interests, opinions (AIOs)] that are less frequently incorporated. With all variables included in the Tobit regression, sex, trip duration, frequency, number of cycling variants practised, visiting cycling websites, and practicing road bicycle racing or mountain bike influence cycling expenditure positively. A negative association is found with competitive riding and cycling drop out. It is suggested that marketers of cycling services and cycling apparel should meet the cyclist's need for identification instead of focusing solely on socio-demographic factors.